Neutron and X-ray scattering studies of magnetism in non-superconducting PrBa2Cu3O6+x - Boothroyd, A (2000)
I give a short review of neutron and X-ray scattering experiments undertaken to study the magnetic properties of non-superconducting PrBa2Cu3O6+x. The measurements have confirmed the magnetic ordering of the Pr sublattice at temperatures below T-Pr approximate to 20 K, and have revealed an incommensurate magnetic structure with a long period (similar to 600 Angstrom) involving both the Pr and Cu spins. The Cu spins in this Pr ordered phase are found to be non-collinear. Taken as a whole, the results provide strong evidence for a substantial magnetic coupling of the pseudodipolar type between the Pr and Cu ions. The effect of this coupling is also evident in the spectrum of low energy magnetic excitations determined by neutron inelastic scattering. (C) 2000 Elsevier Science S.A. All rights reserved.